Utilization of Digital Accounting Technology and Quality of Financial Reports in Economic Decision Making in Jenang Kudus MSMEs - Heni Risnawati; Tuti Nadhifah; Jilma Dewi Ayu Ningtyas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of digital accounting technology utilization and financial reporting quality on economic decision-making in Jenang Kudus MSMEs. The research method used is quantitative with a causal explanatory research approach . The research sample is Jenang MSMEs in Kudus engaged in regional culinary specialties, with a purposive sampling technique based on the criteria of businesses that have been operating for at least two years and have financial recording activities. Primary data was obtained through the distribution of Likert-scale questionnaires compiled based on research variable indicators. The research instrument was tested for validity and reliability before being analyzed using SmartPLS. The results show that the use of digital accounting technology does not have a significant effect on economic decision-making. Conversely, the quality of financial reports has been shown to have a positive and significant effect on economic decision-making. This finding confirms that the quality of accounting information is more decisive for the success of decision-making than the use of digital accounting technology alone.